The influence of minimalist and maximalist footwear on the kinetics and kinematics of running. (2nd January 2016) - Sinclair, Jonathan; Fau-Goodwin, James; Richards, James; Shore, Hannah
Abstract : Minimalist footwear has been the subject of much attention in footwear research. More recently, maximalist footwear, which feature an oversized midsole have been developed. The aim of the current investigation was to compare the kinetics and kinematics of running in minimalist, maximalist and conventional footwear. Twelve male runners ran over an embedded force platform at 4.0 m s −1 in the three footwear conditions. Lower limb kinematics were collected using an eight-camera motion capture system, and tibial accelerations were obtained using an accelerometer. Differences in kinetics and kinematics between footwear were examined using one-way repeated measures ANOVA. The results showed that both instantaneous loading rate and peak tibial acceleration were significantly larger in the minimalist (305.58 BW/s and 9.54 g) compared to the maximalist (141.67 BW/s and 7.99 g) and conventional (127.30 BW/s and 6.73 g) footwear. In addition, peak tibial internal rotation was significantly larger in the minimalist (9.64°) compared to conventional (6.88°) footwear. These findings indicate that minimalist footwear may place runners at increased risk from chronic injury. Further work is, nonetheless, required using runners who habitually utilize these footwear before these findings can be truly substantiated.